Microscope imaging mass spectrometry with a reflectron - Burleigh, RJ; Guo, A; Smith, N; Green, A; Thompson, S; Burt, M; Brouard, M (AIP Publishing, 2020)
A time-of-flight microscope imaging mass spectrometer incorporating a reflectron was used to image mass-resolved ions generated from a 270 μm diameter surface. Mass and spatial resolutions of 8100 ± 700 m/Δm and 18 μm ± 6 μm, respectively, were obtained simultaneously by using pulsed extraction differential acceleration ion optical focusing to create a pseudo-source plane for a single-stage gridless reflectron. The obtainable mass resolution was limited only by the response time of the position-sensitive detector and, according to simulations, could potentially reach 30 200 ± 2900 m/Δm. The spatial resolution can be further improved at the expense of the mass resolution to at least 6 μm by increasing the applied extraction field. An event-triggered fast imaging sensor was additionally used to record ion images for each time-of-flight peak resolved during an experimental cycle, demonstrating the high-throughput capability of the instrument.